STRATEGI PEMASARAN DAMPAK PANDEMI COVID-19 BERDASARKAN ANALISIS SWOT PADA PT. INDOLAKTO DISTRIBUSI SOLO - Dina Prasetyaningrum (Universitas Bina Taruna Gorontalo, 2023)
Companies need to make strategic and policy decisions in handling the impact of the Covid-19 pandemic so that goals can be achieved according to the company's vision and mission. Good strategic planning is a very useful tool for running this business effectively and efficiently, which in its preparation requires a comprehensive design to the chosen implementation and control. Research using the SWOT analysis method was carried out at PT. Indolakto Solo Distribution. The research aims to determine internal IFAS (Internal Strategic Factor Analysis Summary) and external EFAS (External Strategic Factor Analysis Summary) factors using the SWOT method and determine marketing strategies using the SWOT method. The results obtained include the strengths factors with a score of 3.16 while the weaknesses factors have a score of 0.54 with a total IFAS of 1.31. Opportunity factors have a score of 2.53 and threat factors have a score of 0.89 with a total EFAS score of 0.82. The matrix is ​​at the value of the IFAS matrix is ​​strength (Strenghts) with a value of 2.62 and from the EFAS matrix is ​​an opportunity (Oportunity) is a value of 1.64. The recommended strategy is the Strengths and Opportunities strategy, also known as the SO strategy, which uses strengths to overcome opportunities. The IE Matrix strategy and the SWOT diagram show Quadrant I which means a favorable situation because the company has opportunities and strengths so that it can take full advantage of opportunities so that it is able to implement strategies that support aggressive growth policies.